Recent Patents on Conical Pick and Flat Pick for Coal Mining - Wang, Yanxiang; Yang, Daolong; Xing, Bangsheng; Yu, Wenqiang; Guo, Jie; Xu, Hao (Recent Patents on Mechanical Engineering, 2020)
Background: Coal mining machines are the primary equipment used for the comprehensive mining of medium and thick coal seams. A shield machine is used to modify the geological structure of the soil, especially in urban subway tunnel engineering. The cutting and tunneling equipment have greatly improved the efficiency of coal seam mining and rock tunneling construction, but the consumption of picks in mining and tunneling is very high. Objective: In order to reduce the consumption of picks, it is necessary to obtain the change of temperature inside the pick in the process of cutting. Methods: This paper introduces a temperature measurement method to measure the temperature inside the conical and flat pick to provide a reference for the design and manufacture of picks. Results: The temperature measurement method used in flat and conical pick can obtain the temperature change inside the pick under the actual working condition, which has a considerable guiding significance to promote the development of coal mining. Conclusion: This study provides an important basis for the safety of mining operations and for prolonging the service life of picks. It has a strong innovation value and broad practicality.
Keywords: embedded thermosensitive sensor